Fatal poisoning with the antidepressive agent opipramol - Skopp, Gisela; Miltner, Erich; Aderjan, Rolf (Forensic science international, 1996)
An ingestion of an unknown quantity (⩽3000 mg) of opipramol dihydrochloride in a suicide case is described. Quantitation of opipramol and its deshydroxyethyl metabolite was performed simultaneously after liquid-liquid extraction from alkalinized samples prior to HPLC analysis. Postmortem concentrations of opipramol and of the metabolite in body fluids and organs are given. The distribution pattern of opipramol in tissue was comparable to findings from animal studies. The results showed the high uptake of opipramol in parenchymal tissues resulting in a low blood concentration. A possibly low contribution of deshydroxyethyl opipramol to the antidepressive effect may be concluded as the concentration was considerably lower in brain compared to other organs.
Elektronische Reproduktion der Druck-Ausgabe 1. März 1999
Gesehen am 15.08.2023